Định dạng một hệ thống tích hợp CAD/CAM - Đặng, Vũ Giao (Bộ Giáo dục và Đào tạo, 2013)
In the present paper, a module of CAD-CAM in mechanical Engineering is presented. A basic conception of system for processing Part Geometry is determined. Many purposes have been developed in the automatic design of mechanical structure as well as in the Manufacturing process planning. This work is the third part of the research concerning:"The software intcgrated System in Mechanical Engineering" which has been studied by the author from 1982.